Understanding the Enzymatic Synthesis of a New Biolubricant: Decane-1,10-diyl bis(2-methylpentanoate) - Salvadora Ortega-Requena; Fuensanta Máximo; María Claudia Montiel; María Gómez; María Dolores Murcia; Josefa Bastida (Molecules)
The value of branched esters comes from the special properties they have in cold environments, which allow them to remain liquid over a wide range of temperatures. These properties make them useful for application in the cosmetic industry or as lubricant additives. This paper presents the studies carried out to ascertain the operational feasibility of the enzymatic esterification of 2-methylpentanoic acid (MPA) with 1,10-decanediol (DD), with the objective of obtaining a novel molecule: decane-1,10-diyl bis(2-methylpentanoate) (DDBMP). The enzymatic reaction is conducted in a thermostated batch reactor, utilizing the commercially available immobilized lipase Lipozyme® 435 in a solvent-free medium. The reaction conversion is determined by an acid number determination and a gas chromatographic analysis. The most optimal result is achieved at a temperature of 80 °C, a biocatalyst concentration of 2.5% (w/w), and a non-stoichiometric substrate relation. A preliminary economic study and the calculation of Green Metrics has established that the operation with a 30% molar excess of acid is the best option to obtain a product with 92.6% purity at a lower cost than the other options and in accordance with the 12 Principles of Green Chemistry. The synthetized diester has a viscosity index of 210, indicating that this new molecule can be used as a biolubricant at extreme temperatures.